Enhancing cancer immunotherapy: Nanotechnology-mediated immunotherapy overcoming immunosuppression - Yunna Chen; Qianqian Zhou; Zongfang Jia; Nuo Cheng; Sheng Zhang; Weidong Chen; Lei Wang (Elsevier, 2024)
Immunotherapy is an important cancer treatment method that offers hope for curing cancer patients. While immunotherapy has achieved initial success, a major obstacle to its widespread adoption is the inability to benefit the majority of patients. The success or failure of immunotherapy is closely linked to the tumor's immune microenvironment. Recently, there has been significant attention on strategies to regulate the tumor immune microenvironment in order to stimulate anti-tumor immune responses in cancer immunotherapy. The distinctive physical properties and design flexibility of nanomedicines have been extensively utilized to target immune cells (including tumor-associated macrophages (TAMs), T cells, myeloid-derived suppressor cells (MDSCs), and tumor-associated fibroblasts (TAFs)), offering promising advancements in cancer immunotherapy. In this article, we have reviewed treatment strategies aimed at targeting various immune cells to regulate the tumor immune microenvironment. The focus is on cancer immunotherapy models that are based on nanomedicines, with the goal of inducing or enhancing anti-tumor immune responses to improve immunotherapy. It is worth noting that combining cancer immunotherapy with other treatments, such as chemotherapy, radiotherapy, and photodynamic therapy, can maximize the therapeutic effects. Finally, we have identified the challenges that nanotechnology-mediated immunotherapy needs to overcome in order to design more effective nanosystems.